2015
DOI: 10.1007/s00126-015-0600-5
|View full text |Cite|
|
Sign up to set email alerts
|

Zn and Pb mobility during metamorphism of sedimentary rocks and potential implications for some base metal deposits

Abstract: Comprehension of the genesis of Pb-Zn ore systems is currently limited by a poor understanding of where these metals are sourced from. Our study of metal mobility during regional metamorphism in the Mt. Lofty Ranges, South Australia, demonstrates that in staurolite-absent siliciclastic metasedimentary rocks, biotite contains >80 % of the bulk rock Zn, as well as a considerable proportion of the total Pb. Fluid flow through these metasedimentary rocks led to a continuous depletion of Pb and Zn on a mineral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The lack of significant deposition of synkinematic sulfides within the ultramylonites does not support the large presence of S-complexes in the second fluid, suggesting alternatively the involvement of a silicate crustal component as source of the fluid. It has been demonstrated that Zn-bearing biotite and chlorite can host large amounts of bulk Zn content in siliciclastic metasedimentary rocks [62] and altered/metasomatized mafic rocks [63], respectively. In order to explain the Zn enrichment together with the large K, Al, Ti, and Fe content recorded by the most deformed sectors of the shear zone, it is argued that dissolution of crustal biotite more likely governed the composition of the second fluid phase.…”
Section: Evidence For Different Stages Of Fluid-rock Interactionmentioning
confidence: 99%
“…The lack of significant deposition of synkinematic sulfides within the ultramylonites does not support the large presence of S-complexes in the second fluid, suggesting alternatively the involvement of a silicate crustal component as source of the fluid. It has been demonstrated that Zn-bearing biotite and chlorite can host large amounts of bulk Zn content in siliciclastic metasedimentary rocks [62] and altered/metasomatized mafic rocks [63], respectively. In order to explain the Zn enrichment together with the large K, Al, Ti, and Fe content recorded by the most deformed sectors of the shear zone, it is argued that dissolution of crustal biotite more likely governed the composition of the second fluid phase.…”
Section: Evidence For Different Stages Of Fluid-rock Interactionmentioning
confidence: 99%
“…The Syncline) and created an (S 3 ) crenulation (Offler and Fleming, 1968;Mancktelow, 1990;. Metamorphism is of the low-P and high-T type ranging from the greenschist facies (~350-400 °C) in the north and west to the upper amphibolite facies (~540-630 °C) in the south and east (Fleming and White, 1984;Mancktelow, 1990;Sandiford et al, 1990;Dymoke and Sandiford, 1992;Oliver et al, 1998;Foden et al, 1999), with local areas of migmatite around syntectonic igneous intrusions (Hammerli et al, 2015). The syntectonic granites are mostly confined to the core of the orogen (eastern Mt Lofty Ranges, Fleurieu Peninsula and Kangaroo Island) where heat provided by these intrusions formed a metamorphic gradient (Foden et al, 1999).…”
Section: Regional Geologymentioning
confidence: 99%
“…However, it is important to acknowledge that non-sulfides could have potentially been a sink for these base metals as well. Hammerli et al (2015) evaluated the potential mobilization of Pb and Zn in staurolite-and sulfide-absent metasedimentary rocks in the eastern part of the Kanmantoo Trough during metamorphism.…”
Section: Arsenic Can Show Large Compositional Variations In Pyrite Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have established that likely metal sources for Pb-Zn in base metal deposits include (1) sedimentary basins (Leach et al, 2005), (2) crystalline basements (Russell, 1978;Oliver et al, 2006), and (3) the leaching of metals by fluid flow during regional metamorphism (Lebedev and Nagaytsev, 1980;Haack et al, 1984;Hammerli et al, 2015). For Imiter, 187 Os/ 188 Os values lower than 0.2 are considered by Levresse et al, (2004) as representative of a mantle source.…”
Section: Source Of Metalsmentioning
confidence: 99%